MODERN VIEWS ON THE MECHANISMS OF LABOR. OVERVIEW - Галина Александровна Ушакова; Любовь Никитична Петрич (The Publishing House Medicine and Enlightenment, 2016)
Presents modern morphological, physiological, biochemical and biophysical changes in the mother - pregnant uterus - placenta - fetus, providing uterine and labor. Labor dominant is an indicator of readiness for delivery. However, an integrated clinical marker of the labor dominant remains one of the unsolved mysteries of obstetrics.